Mental health stakeholders' perception toward mental illness in West Java - Kartika Farahdilla Fitri; Shelly Iskandar; Achadiyani Achadiyani (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background: Mental illness is predicted to rise and will have been as second rank in Global Burden Disease by year of 2020. Two thirds sufferer do not seek and receive a care. Stigma, discrimination, and ignorance about mental health are true obstacles still happening in Indonesia. Mental health stakeholders have essential role for making and applying policy in order to improve sufferer's quality of life. Their perception influence the intervention of mental health. The purpose of this study is to describe mental health stakeholders' perception toward mental illness in West Java.Methods: This was cross-sectional descriptive study which was conducted using questionnaire as secondary data. Sampling method was taken by using total sampling. Subject of this study were 75 representatives of stakeholder working at health department, local general hospital, social service department, and local government regency/city of West Java.Results: Result of this study showed good perception of mental health stakeholders. Respondents had a good perception toward cause and treatment of mental illness.Conclusions: Respondents' perception showed a good understanding toward mental illness. Stakeholders were expected to implement the policy and intervention program in order to handle mental health problem in West Java.